Dowling–Degos disease in a 23-year-old Jordanian male: a case report - Hamdah Hanifa; Aya Mohannad Hamdan; Ansam Zakaria Baniamer; Jihan Mohammed Muhaidat; Sultan Hussein Al-Sahoud; Mohammad Raed AlGhzawi; Mohammad Tareq Alfaqeh (Journal of Medical Case Reports)
Abstract Background Dowling–Degos disease is a rare genodermatosis disorder that presents as an autosomal dominant trait during late childhood or in adolescence and is also known as reticulate pigmented anomaly of flexures, Dowling–Degos–Kitamura, or dark dot disease. Dowling–Degos disease is characterized by acquired reticular hyperpigmentation, and manifests as a clustered or reticulated pattern mainly at flexural sites, especially in the folds of the skin with comedone-like follicular papules and pitted perioral scars. It appears in both genders but is more likely in females. Case presentation A 23-year-old Jordanian male presented with progressive hyperpigmented macules and papules on his forehead, initially managed with Triderma cream without improvement. Histopathological examination via punch biopsies revealed features consistent with Dowling–Degos disease, excluding malignancy. Treatment was transitioned to sunblock, depigmenting agents (Isis Unit One 4 White), and moisturizers, resulting in significant fading of lesions after 8 months. Genetic counseling was provided owing to the hereditary nature of Dowling–Degos disease, and long-term management strategies were emphasized. Conclusion Dowling–Degos disease is a rare genodermatosis that can cause significant psychological distress and a decline in quality of life. Despite challenging treatment, a multidisciplinary approach is essential for improving patient outcomes and managing the elevated risk of skin cancers.